Gas separation in industrial bulk chemistry and relevance for transitioning to industrial plasma chemistry - Volker Hessel; Nguyen Van Duc Long; Marc Escriba-Gelonch; Jose Osorio Tejada; Muhammad Yousaf Arshad; Anubhav Sabharwal; Gabriele Centi; Annemie Bogaerts; Evgeny Rebrov; Peter H. Seeberger (Chemical Engineering Journal, 2026)

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Digital twin modelling of lettuce growth under extreme earth conditions on earth: a very first step to plant growth in outer space - Shu Liang; Nguyen Van Duc Long; Stephen Lantin; Marc Escribà-Gelonch; Volker Hessel (Clean Technologies and Environmental Policy, 2025)

Digital twin for lettuce growth in six climate zones (‘Climate 2050′) - Shu Liang; Nguyen Van Duc Long; Mst Irin Parvin; Marc Escribà-Gelonch; Stephen Lantin; Volker Hessel (Computers and Electronics in Agriculture, 2025)

Subcutaneous zilucoplan: Evaluation of reproductive toxicology - Marie Lemper; C. Marc Luetjens; Antje Fuchs; Peter Hall; François-Xavier Mathy; Jeff Long; Joy Cavagnaro; Sucharita Roy; Evan A. Thackaberry; Petra Duda (Reproductive Toxicology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Physiological adaptation of the diatom Pseudo-nitzschia delicatissima under copper starvation - Marc Long; Aurélie Lelong; Eva Bucciarelli; Fabienne Le Grand; Hélène Hégaret; Philippe Soudant (Marine Environmental Research, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Canopy structure and light interception partitioning among shoots estimated from virtual trees: comparison between apple cultivars grown on different interstocks on the Chinese Loess Plateau - Wei-Wei Yang; Xi-Long Chen; Marc Saudreau; Xiao-Yun Zhang; Man-Rang Zhang; Hang-Kong Liu; Evelyne Costes; Ming-Yu Han (Trees, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

PCR primers for microsatellite loci in a Madagascan waterbird, the Sakalava Rail (Amaurornis olivieri) - Edward G. Brede; Peter Long; Sama Zefania; Marc Rabenandrasana; Tamás Székely; Michael Bruford (Conservation Genetics Resources, 2010)

Species richness and abundance of native leaf miners are affected by the presence of the invasive horse-chestnut leaf miner - Christelle Péré; Sylvie Augustin; Rumen Tomov; Long-hui Peng; Ted C. J. Turlings; Marc Kenis (Biological Invasions, 2010)